Protecting and promoting livelihoods of the excluded through the community work programme: a comparative case study of Munsieville and Bekkersdal - Masondo, Themba (My University, 2018)
The idea of the government acting as an Employer of Last Resort (ELR), commonly known as ‘public works’, has become a prominent feature of the ‘impulse for social protection’ in the global South. The dissertation focuses on a long-term ELR programme in South Africa called the Community Work Programme (CWP) – a distinctively and innovatively designed component of the orthodox Expanded Public Works Programme (EPWP). Based on field research involving the triangulation of a survey questionnaire, in-depth semi-structured interviews, focus groups, and ethnographic non-participant observation – this study adopts the comparative case study approach, imbued in the extended case method, to investigate the CWP’s potentialities in protecting and promoting livelihoods of the excluded in Munsieville and Bekkersdal—located in the West Rand region of the Gauteng Province, South Africa The central question posed in this dissertation is whether the CWP has other transformative potentialities beyond its ameliorative role. The dissertation advances three connected arguments. First, the dissertation argues that in addition to protecting livelihoods, the CWP possesses transformative potential in fostering development from below. The CWP participants in Munsieville tended to possess greater autonomous capabilities in adapting the CWP to respond to a myriad of local social challenges. Secondly, the dissertation argues that the mainstream theoretical approaches to livelihood promotion through the ELR tend to ignore cooperative development as a potential vector for promoting livelihoods of the excluded. In this respect, the dissertation presents the case of three nascent CWP-linked cooperatives in Munsieville to illustrate this argument. Lastly, the dissertation argues that the operationalisation of the Organisation Workshop (OW) methodology in Munsieville helps clarify the significant variance in the outcomes of the CWP in the two townships. Key words: community work programme, employer of last resort, organisation workshop, protecting livelihoods and promoting livelihoods.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy.
Keywords: Economic development projects--South Africa; Public works--South Africa; Unemployment--South Africa; Local government--South Africa